Problematizing the Emergence of Household Food Security in England - Midgley, Jane L. (The International Journal of Sociology of Agriculture and Food, 2013)
Household food security is a term associated with social welfare and the distribution of resources within society. It is also an organizing metaphor that is highly political and context dependent in its construction and deployment. How the concept emerges into new situations is often overlooked. This article problematizes the recent emergence of household food security in England, a feature closely linked to the food policy developments of the UK Government (2007–2010). I explore household food security in England through a discourse analysis of published policy texts and semi-structured interviews with third-sector practitioners. These reveal the tensions surrounding the introduction of household food security into this domestic policy setting. I show how policymakers used the concept strategically, and how the discursive and institutional legacies of food poverty and the welfare state constrained the wider adoption of household food security in this contemporary setting.